The Efficacy of Evacuating The Anterior Chamber on Lowering The Viscoelastic Related Intraocular Pressure Rise after Cataract Surgery - Alagöz, Gürsoy; Kükner, Şahap; Serin, Didem; Çelebi, Serdal; Yalçın, Ahmet (Fırat University, 2007)
Objective: To evaluate the efficacy of evacuating the anterior chamber by pressing on the posterior side of the corneal incision on lowering the intraocular pressure (IOP) and relieving symptoms in patients with viscoelastic related IOP rise. Materials and Methods: Fifty patients with an IOP of ≥25 mmHg and symptoms related to high IOP caused by viscoelastics at the 6th postoperative hour following phacoemulsification were included in the study. Anterior chambers were evacuated by exerting gentle pressure on the posterior side of the corneal incision. Visual acuity, IOP, corneal edema, and pain scores of all the patients were recorded on the day before the surgery, at the 6th postoperative hour, 15 minutes after evacuation, and on the 1st, 3rd and 7th postoperative days. Results: The average IOP which was recorded to be 17.2±2.5 mmHg on the day before surgery was 32.42±5.3 mmHg at the 6th postoperative hour. The IOP values were reduced to 8.50±3.2 mmHg 15 minutes after evacuation of the anterior chamber. IOP was found to be 16.27±2.5 mmHg, 16.20±1.8 mmHg and 16.45±2.3 mmHg on the 1st, 3rd and 7th postoperative days, respectively. The IOP values at the 6th postoperative hour were significantly higher from the values before surgery and after the evacuation. Evacuating the anterior chamber by gentle pressure on the incision site in patients with increased IOP, corneal edema, reduced visual acuity, and ocular pain related to viscoelastics in the early postoperative period is a rapid, efficient, reliable, and cost-effective method ©2007, Firat University, Medical Faculty

Amaç: Fakoemülsifikasyon cerrahisi uygulanan ve cerrahi sonrası erken dönem de viskoelastik maddeye bağlı GİB artışı olan olgularda, korneal kesinin arka dudağına basınç uygulayarak ön kamara içeriğini boşaltmanın GİB'nı düşürmede ve semptomları düzeltmede ki etkinliğini araştırdık. Gereç ve Yöntem: Fakoemülsifikasyon sonrası 4. saatte viskoelastik maddeye bağlı GİB 25 mmHg ve üzerinde olan ve artmış GİB'na bağlı şikayeti bulunan 50 hasta çalışmaya alındı. Biyomikroskop yardımı ile korneal tünel kesisi arka dudağına kontrollü bir şekilde basınç uygulanıp ön kamara içeriğinin yara yerinden dışarı çıkması sağlandı.Tüm olguların cerrahiden bir gün önce, cerrahi sonrası 6. saatte, işlemden sonra 15. dakika ve cerrahiden sonra 1., 3. ve 7. gün görme düzeyleri, GİB ölçümleri, korneal ödem ve ağrı derecelendirilmeleri yapıldı. Bulgular: Hastaların ameliyat öncesi 1.gün GİB'ları ortalama 17,2±2,5 mmHg iken ameliyat sonrası 6. saatte 32,42±5,3 mmHg olarak tespit edildi. Ön kamara mayisinin boşaltılmasından 15.dakika sonra ortalama GİB 8.50± 3,2 mmHg olarak ölçüldü. Cerrahi sonrası 1. gün 16,27±2,5 mmHg, 3. gün 16,20±1,8 mmHg, 7. gün 16,45±2,3 mmHg olarak tespit edildi. Olguların GİB'ları cerrahi sonrası 6. saatte cerrahi öncesi 1. günkü değerlerden ve işlem öncesi değerler de işlem sonrasından anlamlı derecede yüksek olarak bulundu. Kesi yerinden ön kamara içeriğinin boşaltılmasının katarakt cerrahisi sonrası erken dönem GİB yükselmesi ve artan GİB'nın sebep olduğu korneal ödem, görme azlığı ve göz ağrısını ortadan kaldırmada hızlı, güvenilir, etkin ve ucuz bir yöntem olduğu görüşündeyiz. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Katarakt Cerrahisinde Viskoelastik Maddeye Bağlı Yükselen Göz İçi Basıncının Düşürülmesinde Korneal İnsizyon Bölgesinden Viskoz Ön Kamara Mayisi Boşaltılmasının Etkinliği